Layer-engineered interlayer excitons - Tan, Qinghai (2022)
Photoluminescence (PL) from excitons serves as a powerful tool to characterize the optoelectronic property and band structure of semiconductors, especially for atomically thin 2D transition metal chalcogenide (TMD) materials. However, PL quenches quickly when the thickness of TMD material increases from monolayer to few-layers, due to the change from direct to indirect band transition. Here we show that PL can be recovered by engineering multilayer heterostructures, with the band transition reserved to be direct type. We report emission from layer engineered interlayer excitons from these multilayer heterostructures. Moreover, as desired for valleytronic devices, the lifetime, valley polarization, and the valley lifetime of the generated interlayer excitons can all be significantly improved as compared with that in the monolayer-monolayer heterostructure. Our results pave the way for controlling the properties of interlayer excitons by layer engineering.